(untitled) (aSSIST Business Review, 2026)
(1) Background/Purpose: This study examines whether individually approved ingredients in the Korean functional health food industry have successfully created monopoly or oligopoly markets as intended. (2) Methodology: Case analyses were conducted for three representative individually approved ingredients—HemoHim, HT042, and UREX—using STP (Segmentation, Targeting, Positioning) and 4P (Product, Price, Place, Promotion) frameworks. Production statistics from the Ministry of Food and Drug Safety (MFDS) 2023 Production Statistics of Food and Related Products were used to calculate market share across all 167 individually approved ingredients with production records. Correlation and regression analyses were performed to statistically verify identified success factors. (3) Findings: Two of the three case ingredients initially failed due to overly narrow segmentation and targeting strategies. Success was achieved only after broadening the target market. In terms of positioning, all three ingredients established themselves as the ‘first and only’ solution in their functional categories. Statistical analysis confirmed a significant correlation (R² = 0.392) between certification order and market share ranking across all 167 ingredients. (4) Originality/Value: This study provides the first empirical analysis of market performance for individually approved health functional food ingredients over the 20 years since the enactment of the Health Functional Foods Act. Practical implications are offered for R&D and distribution companies considering development of individually approved ingredients.